Approach Coping Mitigates Distress of COVID-19 Isolation for Young Men With Low Well-Being in a Sample of 1,749 Youth From Australia and the USA - Cheng, Phillip (Xin); Park, Haeme R. P.; Gatt, Justine M. (Frontiers in Psychiatry, 2021)
The unprecedented COVID-19 pandemic has led to lockdowns across the world with people being separated from their loved ones including partners, family and friends. Here, using a large sample of 1749 Australians and Americans, we investigated the impact of COVID-19 isolation on younger populations (13-25 years), and the influence of coping strategies and mental wellbeing on this impact. Overall, COVID-19 isolation had a more negative impact on adolescence (13-17 years) than young adulthood (18-25 years), but with no difference apparent between men and women, or between Australian and American residents. However, a deeper analysis revealed a gender-specific effect: the type of coping strategies differentially influenced the negative impact of COVID-19 isolation on men with various levels of wellbeing, an interaction effect not apparent in women. For men with lower levels of mental wellbeing, COVID-19 isolation appeared to have a less negative impact on them if they used approach-oriented coping strategies (e.g., actively focusing on the problem). Our results provide cross-sectional evidence for a differential impact on young men and young women by pandemic isolation. In sum, young men with lower wellbeing levels show greater benefits from using an approach coping strategy, compared to men with higher wellbeing, or women.